Differentiation of Breast Lesions and Distinguishing Their Histological Subtypes Using Diffusion-Weighted Imaging and ADC Values - Maric, Jelena; Boban, Jasmina; Ivkovic-Kapicl, Tatjana; Djilas, Dragana; Vucaj-Cirilovic, Viktorija; Bogdanovic-Stojanovic, Dragana (Frontiers in Oncology, 2020)
Diffusion-weighted imaging (DWI) has not been well explored in differentiation of malignant from benign breast lesions. The aims of this study were to examine the role of apparent diffusion coefficient (ADC) values in differentiation of malignant from benign tumors and distinguishing histological subtypes of malignant lesions, and to determine correlations between ADC values and breast tumors structure. This cohort-study included 174 female patients who underwent contrast-enhanced breast MR examination on a 3T scanner and were divided into two groups: patient group (114 patients with proven tumors) and control group (60 healthy patients). One-hundred-thirty-nine lesions (67 malignant and 72 benign) were detected and pathohistologically analyzed. Differences between variables were tested using chi-square test; correlations were determined using Pearson's correlation test. For determination of cut off values for diagnostic potential, Receiver Operating Characteristic curves were constructed. Statistical significance was set at p<0.05. Mean ADC values were significantly lower in malignant compared to benign lesions (0.68x10-3mm2/s vs. 1.12 x10-3mm2/s, p<0.001). The cut off value of ADC for benign lesions was 0.792 x10-3mm2/s (sensitivity 98.6%, specificity 65.7%), and for malignant 0.993 x10-3mm2/s (98.5%, 80.6%). There were no significant correlations between malignant lesion subtypes and ADC values. DWI is a clinically useful tool for differentiation of malignant from benign lesions based on mean ADC values. The cut off value for benign lesions was higher than reported recently, due to high amount of fibrosis in included benign lesions. Finally, ADC values might have implications in determination of the biological nature of the malignant lesions.